Beyond the Labor Market Paradigm: A Social Network Perspective on Teacher Recruitment and Retention - Baker-Doyle, Kira (Education Policy Analysis Archives, 2010)
This article identifies limits of the dominant labor market perspective (LMP) in research on teacher recruitment and retention and describes how research that incorporates a social network perspective (SNP) can contribute to the knowledge base and development of teacher education, staffing, and professional development approaches. A discussion of current literature on teachers' social networks and a case example of social network perspective research highlight how such research reveals complex social factors that shape teachers' workplace experiences and show the ways in which the labor market perspective tends have a "recruitment-heavy" focus. The article describes how the social network perspective allows researchers to study social workplace concerns from both macro and micro perspectives. This approach can broaden the current focus on recruitment to a more comprehensive understanding of recruitment and retention.